Mitigation of drought stress effects on alfalfa (Medicago sativa L.) callus through CaO nanoparticles and graphene oxide in tissue culture conditions - YAZICILAR, Büşra; NADAROĞLU, Hayrunnisa; ALAYLI, Azize; NADAR, Muthukumar; GEDİKLİ, Semin; BEZİRĞANOĞLU, İsmail (Plant cell, tissue and organ culture, 2024)
Drought stress poses a significant threat to fertile soils worldwide, triggering profound physiological, biochemical, and molecular changes in plants that adversely impact agricultural productivity. This study explores the potential of nanotechnology, specifically Calcium Oxide Nanoparticles (CaO NPs) and Graphene Oxide (GO), to ameliorate the negative effects of drought stress on two distinct alfalfa ecotypes. Seeds from Erzurum and Konya regions were regenerated in the Murashige and Skoog (MS) medium, and ensuing callus formation was induced through 1 mg L −1 2,4-D and 1 mg L −1 kinetin MS medium. The callus samples underwent a one-month treatment with varying concentrations of mannitol (50 and 100 mM), CaO NPs, and GO (0.5 and 1.5 ppm). Results revealed a decrease in dry/wet weight with increasing mannitol concentration, contrasting with an increase in weight under CaO NPs and GO treatment. Proline, DNSA, MDA, and H 2 O 2 exhibited proportional increases under drought stress, while CaO NPs and GO treatments mitigated these effects. Physiological and biochemical analyses identified optimal conditions for Erzurum as 50 mM mannitol/2 CaO NPs/0.5 ppm GO, and for Konya as 50 mM mannitol/0.5 ppm GO. Gene expression analysis indicated up-regulation of mtr-miR159 and mtr-miR393 with heightened drought stress, with down-regulation observed in CaO NPs and GO treatments. Scanning Electron Microscopy (SEM) and Confocal Laser Scanning Microscopy (CLSM) confirmed Ca 2+ accumulation in alfalfa tissues. In conclusion, CaO NPs and GO treatments exhibited a significant reduction in the adverse effects of drought stress on alfalfa callus under tissue culture conditions. This research sheds light on the potential of nanotechnological interventions to alleviate the impact of environmental stressors on crop plants, opening avenues for sustainable agriculture in the face of changing climatic conditions. Further investigations are warranted to elucidate the underlying mechanisms and scalability of these findings for field applications. Key message CaO NPs and GO enhanced the tolerance of M. sativa callus under drought stress improving biochemical activity, miRNA gene expression, confocal laser scanning, and electronic scanning analysis.